Attitudes of Saudis toward social media use during emergencies and disasters: A community-based study - Mashal Mnahi Al Shebani; Anas A Khan (Wolters Kluwer Medknow Publications, 2021)
Introduction: Social media is the most commonly used method of communication during emergency and disaster events. The prompt contribution of social media in emergency management has lately captured the imagination of governmental organizations and researchers. This study explores the attitudes of Saudis toward social media use during emergency and disaster events. Materials and Methods: A cross-sectional study was conducted via an electronic questionnaire sent to all Saudis across all regions of Saudi Arabia. Data were collected using a valid self-administered questionnaire. The questionnaire solicited demographic details of survey participants and their attitudes toward social media, particularly regarding emergency and disaster events. Results: A total of 385 respondents were included in this study. Respondents reported that they used TV news channels (89%), followed by local radio (82%), online news (61%), and social media (43%). Most respondents used WhatsApp (61.0% always and 20.0% frequently). Significant differences in the general use of social media among participants from different age groups (P < 0.001), gender (P < 0.012), and education levels (P < 0.0001) were noted. About 35% of respondents used social media for information during emergencies and disasters. Of the participants who used social media in this context, 86% sought information regarding weather conditions or warnings/advisories. A majority of the participants indicated that the information extant on social media during emergencies and disasters is available more quickly and is more accessible when compared with other channels (86.4%, 77.6%). A majority of the participants exhibited a positive attitude toward the future use of social media for information on emergencies and disasters (81.8%, mean = 4.16). Approximately 57.7% of participants stated that they were unaware of Facebook Safety Checks, and 35% of them were unaware of Twitter Alerts. Conclusion: This study revealed that the attitudes of Saudis toward the use of social media either for general use or during emergencies were similar to those in other studies.